(untitled) (Applied Biological Research, 2015)
Present study was aimed to assess plant growth promoting activity of rhizobacteria isolated from mid hill region of Himachal Pradesh (India). Onehundredrhizobacteriawereisolatedandafterreplicaplating on 3 media viz., chrome-azurol-S (CAS), Pikovskaya’s and N-free Jensen’s medium, 26 isolates were further characterized on the basis of functional plant growth promoting traits viz., phosphorus solubilization, indole-3-acetic acid (IAA) production, siderophore production, growth on N-free medium, lytic enzymes production as well as antifungal activity against Alternaria solani, Fusarium oxysporum f. sp. lycopersici, Pythium aphanidermatum, Phyto production (95 µg mL-1). The highest siderophore production (209% SU) was observed in isolate S14. Of the 26 isolates, 18 were nitrogen fixers while 23 and 20 isolates showed chitinase and protease activity, respectively. On the basis of in vitro screening, 10 most efficient isolates were screened for growth promotion on tomato under net house conditions. Strain S25 exhibited highest seed germination (78%), root length (16.9 cm), root dry weight (1.32 g plant-1), shoot length (31.5 cm) and shoot dry weight (6.3 g plant-1). Random amplified polymorphic DNA (RAPD) fingerprinting was performed to ascertain the genetic variability among the ten most efficient PGPR. Overall strain S25, identified as Bacillus subtilis on the basis of biochemical and molecular characterization, proved most efficient. This strain could be used as an PGPR inoculant having multiple PGP-traits for plant growth promotion under mid hilly conditions.